Nature And Reasons For The Origin Of Problem Loans - Izbosarov Boburzhon Bakhriddinovich; Ulmasoy Akhmedova Khusan kizi (Global Scientific Publishing, 2025)
The article is devoted to the analysis of methods of managing problem loans in commercial banks. It systematizes the key factors that contribute to the formation of problem debt. The theoretical aspects of managing problem assets are considered. Also, measures are proposed aimed at reducing the share of problem loans in Uzbek commercial banks, based on the experience of European countries
Keywords: problem; loan; borrower; loan repayment